The essential Berkeley and neo-Berkeley - Berman, David (London : Bloomsbury Academic, 2022)
The Essential Berkeley and Neo-Berkeley is an introduction to the life and work of one of the most significant thinkers in the history of philosophy and a penetrating philosophical assessment of his lasting legacy. Beyond solely an introduction, Berman also gives us a broader and deeper appreciation of Berkeley as a philosopher. He argues for Berkeley's work as a philosophical system with coherence and important key themes hitherto unexplored and provides an analysis of why he thinks Berkeley's work has had such lasting significance. With a particular focus on Berkeley's dualist thinking and theories of 'mental types', Berman provides students and scholars with a key to unlocking the significance of this work. This introductory text will provide an insight into Berkeley's full body of work, the distinctiveness of his thinking and how deeply relevant this key thinker is to contemporary philosophy..
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Berkeley, George, -- 1685-1753; Philosophy -- Anglo-Irish.; Philosophy -- Christianity